Goat science and production - Solaiman, Sandra Golpashini, 1952- (Wiley-Blackwell, 2010)
Goat science and production presents comprehensive, state-of-the-art information on the science of goats and goat production for meat, dairy, and fiber. Chapters provide a fundamental understanding of the goat anatomy and physiology as well as production issues such as welfare, disease management, and feeding. Goat science and production is an essential introduction and reference to this increasingly important production animal.